2021
DOI: 10.1155/2021/8493505
|View full text |Cite|
|
Sign up to set email alerts
|

Application Experience and Patient Feedback Analysis of 3D Printed AFO with Different Materials: A Random Crossover Study

Abstract: Purpose. This study is aimed at analyzing the application experience and feedback of the patients with poststroke ankle dorsiflexion disorders for 3D printed AFO with three different materials. Methods. 15 patients were randomly divided into three groups; 3D printed AFO with 3 different materials (PA2200, Somos NeXt, and PA12) was used to each group, according to the crossover study design, in order to ask the three groups of patients to use three different materials of 3D printed AFO. Assessment was taken by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…For each paper, when present, it is reported the AFO type(s), the customization criteria, the materials, the functional data/parameters, and the main outcome. Comfort assessment or other subjective scores are also reported Authors/year Population (size) AFO type/ customization criteria Material Motor tasks Functional parameters Other scores Main outcome Waterval et al 2021 [ 56 ] unilateral plantar flexor weakness (9) dorsal leaf spring AFO Spring leaf Stiffness customizable energy cost optimized (Ankle7, OttoBock) carbon fiber walking spatio-temporal parameters GRFs hip, knee, ankle kinematics and kinetics peak vertical GRF of the contralateral leg significantly reduced and symmetry improved (AFO vs. no AFO) Waterval et al 2021 & 2020 [ 32 , 33 ] calf muscle weakness (34) dorsal leaf spring AFO Spring leaf Stiffness customizable (Ankle7, OttoBock)e carbon fiber walking spatio-temporal parameters hip, knee, ankle kinematics and kinetics energy cost reduction in energy cost (AFO optimized stiffness vs. non optimized) Kerkum et al 2021 [ 35 ] healthy subjects (12) dorsal leaf spring AFO Spring leaf Stiffness customizable (Ankle7, OttoBock) carbon fiber walking Ankle-foot kinematics work and power Total ankle-foot power increase with increasing footplate stiffness Lin et al 2021 [ 57 ] post-stroke drop-foot (12) 1. energy-Storage 3D Printed AFO 2. anterior-support AFO PLA + nylon+titanium thermoplastic walking spatio-temporal parameters pelvis, hip, knee, ankle kinematics (sagittal plane) Evaluation of satisfaction (QUEST) increased gait velocity and stride length (AFO1 vs. AFO2; AFO1 vs. barefoot) improved satisfaction (AFO1) Meng et al 2021 [ 58 ] post-stroke drop-foot (15) morphology PA2200 Somos NeXt PA12 NA NA …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For each paper, when present, it is reported the AFO type(s), the customization criteria, the materials, the functional data/parameters, and the main outcome. Comfort assessment or other subjective scores are also reported Authors/year Population (size) AFO type/ customization criteria Material Motor tasks Functional parameters Other scores Main outcome Waterval et al 2021 [ 56 ] unilateral plantar flexor weakness (9) dorsal leaf spring AFO Spring leaf Stiffness customizable energy cost optimized (Ankle7, OttoBock) carbon fiber walking spatio-temporal parameters GRFs hip, knee, ankle kinematics and kinetics peak vertical GRF of the contralateral leg significantly reduced and symmetry improved (AFO vs. no AFO) Waterval et al 2021 & 2020 [ 32 , 33 ] calf muscle weakness (34) dorsal leaf spring AFO Spring leaf Stiffness customizable (Ankle7, OttoBock)e carbon fiber walking spatio-temporal parameters hip, knee, ankle kinematics and kinetics energy cost reduction in energy cost (AFO optimized stiffness vs. non optimized) Kerkum et al 2021 [ 35 ] healthy subjects (12) dorsal leaf spring AFO Spring leaf Stiffness customizable (Ankle7, OttoBock) carbon fiber walking Ankle-foot kinematics work and power Total ankle-foot power increase with increasing footplate stiffness Lin et al 2021 [ 57 ] post-stroke drop-foot (12) 1. energy-Storage 3D Printed AFO 2. anterior-support AFO PLA + nylon+titanium thermoplastic walking spatio-temporal parameters pelvis, hip, knee, ankle kinematics (sagittal plane) Evaluation of satisfaction (QUEST) increased gait velocity and stride length (AFO1 vs. AFO2; AFO1 vs. barefoot) improved satisfaction (AFO1) Meng et al 2021 [ 58 ] post-stroke drop-foot (15) morphology PA2200 Somos NeXt PA12 NA NA …”
Section: Resultsmentioning
confidence: 99%
“…Thirty‐three papers published from 1999 to 2021 were retrieved and found relevant to the topic. In terms of populations investigated, custom AFOs were used for post‐stroke patients ( n = 6) [11, 34, 57, 58, 62, 64], for generic drop‐foot and muscles weakness ( n = 13) [8, 24, 30–33, 39, 40, 44, 50, 51, 56, 59], for lower limb reconstruction ( n = 4) [22, 23, 25, 60], for cerebral palsy ( n = 4) [27, 28, 61, 66], for Charcot–Marie–Tooth ( n = 1) [29], in children with hemiplegia ( n = 2) [63, 65], and in normal/healthy subjects ( n = 3) [7, 35, 43]. Posterior Leaf Spring (PLS) are the most common types of AFOs functionally evaluated and were compared to solid and hinged AFOs, and/or to shod/barefoot conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Here, C d is the curing depth, E is the incident light intensity of the light projected by the projector, E c is the critical light intensity when the resin undergoes a curing reaction, and D p is the projection depth coefficient, a decimal, which is a characteristic of the photosensitive resin itself [22]. When the photosensitive resin is cured by specific light irradiation, the oligomer in the photosensitive resin absorbs the energy of photons and undergoes a photocuring chemical reaction.…”
Section: D Printing Algorithmmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%